2017
DOI: 10.1155/2017/8362613
|View full text |Cite
|
Sign up to set email alerts
|

Forsaken Foregut: Case Report of Simultaneous Black Esophagus and Ischemic Cholangiopathy

Abstract: Black esophagus or acute esophageal necrosis rarely occurs after severe hemodynamic compromise or low-flow states. Other contributing factors may include corrosive injury from gastric contents and diminished mucosal repair mechanisms. Ischemic cholangitis, another rare clinical entity, is also usually the result of a significant vascular and/or hypotensive insult to the biliary tree. We describe the first case of combined acute esophageal necrosis and ischemic cholangiopathy in a 62-year-old male who completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The role of ischemia is supported by the observation that this disease may occur in combination with other ischemic events that affect the splanchnic circulation, such as ischemic cholangiopathy [12] or hypoxic hepatitis [13], which also result from generalized states of hypoperfusion in patients with similar risk factors for advanced atherosclerosis. Accordingly, the low incidence of this disease compared with other ischemic events (for example, acute coronary syndrome) among susceptible patients could be related to the complex anastomotic vascular network present in the esophageal submucosa.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The role of ischemia is supported by the observation that this disease may occur in combination with other ischemic events that affect the splanchnic circulation, such as ischemic cholangiopathy [12] or hypoxic hepatitis [13], which also result from generalized states of hypoperfusion in patients with similar risk factors for advanced atherosclerosis. Accordingly, the low incidence of this disease compared with other ischemic events (for example, acute coronary syndrome) among susceptible patients could be related to the complex anastomotic vascular network present in the esophageal submucosa.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Of these cases, we managed to extract data from 79 articles having 105 cases of AON (online supplementary table 1). 5–82 Data could not be extracted from (n=13) of the articles containing a total of (n=20) cases 4 83–95. The most common reasons for these were unavailability of complete data or the language being other than English.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] These case studies suggested low systemic perfusion due to alcoholic lactic acidosis, hypothermia, and impaired mucosal defence are major pathological causes of alcohol-induced AEN. [8][9][10][11][12][13][14][15][16] Multiple forensic studies on alcohol-induced AEN have shown hemorrhagic shock resulting from esophageal necrosis is the most common cause of death, followed by cardiac arrest and hypothermia (table 2). [17][18][19][20][21] On autopsy, a black pigmentation involving the distal esophagus with or without Wischnewski lesions (red brownish erosions of the mucosa) and hemorrhagic fluid collection are commonly reported findings related to alcohol-induced AEN (table 2).…”
Section: Pathogenesis and Etiologymentioning
confidence: 94%
“…AEN associated with active alcohol drinking is a rare entity, and only nine cases have been reported in the current literature (table 1). [8][9][10][11][12][13][14][15][16] Upper gastrointestinal hemorrhage, vomiting, abdominal pain and unresponsiveness are common presenting symptoms in these cases with AEN associated with drinking alcohol ranging 2-8 pints daily. [8][9][10][11][12][13][14][15][16] These case studies suggested low systemic perfusion due to alcoholic lactic acidosis, hypothermia, and impaired mucosal defence are major pathological causes of alcohol-induced AEN.…”
Section: Pathogenesis and Etiologymentioning
confidence: 99%
See 1 more Smart Citation